Fertilization of Field-grown and Landscape Palms in Florida - Timothy K. Broschat (EDIS, 2019)
Palms growing in Florida landscapes or field nurseries are subject to a number of potentially serious nutrient deficiencies. These deficiencies are described and illustrated in document ENH1018. Prevention and treatment of these deficiencies is the subject of this document. Chemical symbols used in this document are as follows: N=nitrogen, P=phosphorus, K=potassium, Mg=magnesium, Ca=calcium, Mn=manganese, Fe=iron, B=boron, Cu=copper, Zn=zinc. This document is ENH1009, one of a series of the Environmental Horticulture Department, UF/IFAS Extension. Original publication date September 2005.